Faktor-Faktor Yang Mempengaruhi Konsumen dalam Memilih SPBU Menggunakan Analisa Faktor - Lutfi Despon Suprapto; Sukanta Sukanta (Jurnal Ilmiah Wahana Pendidikan, 2021)
Nowaday national gasoline market becomes tighter with the entrance of foreign retailers to the field. Competition is not only among domestic gas stations but also between local and foreign stations. At this situation, to survive and win the competition retailers should maintain customer satisfaction through serving good service(s) and providing facilities needed. This research aims to determine which service(s) is needed and which one is not as well what facility(s) are necessary, should be available, or can be omitted. For the purpoase, a survey was conducted. Of 211 respondents participated, the results then were analyzed using Faktor Analysis method. The findings are the most important variable to choose a city gas station is the station map and legend clarity and station light sufficiency for out of town gas station.While the most neglible variable is the station dispenser accuracy for both city and out of town gas stations.